2006
DOI: 10.1111/j.1746-1561.2006.00060.x
|View full text |Cite
|
Sign up to set email alerts
|

School Absenteeism and School Refusal Behavior: A Review and Suggestions for School‐Based Health Professionals

Abstract: School absenteeism and school refusal behavior are particularly difficult problems that school health professionals often face. Unfortunately, few recommendations are available to such professionals about how to address this population. In this article, we (1) outline the major characteristics of school absenteeism and school refusal behavior, (2) review school-based health programs that have been designed in part to reduce absenteeism, and (3) provide suggestions for school health professionals regarding indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
78
1
10

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(103 citation statements)
references
References 30 publications
4
78
1
10
Order By: Relevance
“…Some researchers have identified school absenteeism as a complex and a heterogeneous problem that can be influenced by many factors (Kearny, 2008;Kim & Streeter, 2006;& Lauchlan, 2003). Romero (2008) Uche & Maliki (2013) stressed that absenteeism and dropout can be caused by difficult terrain and long distances from school which tempt or force children to withdraw prematurely from school.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some researchers have identified school absenteeism as a complex and a heterogeneous problem that can be influenced by many factors (Kearny, 2008;Kim & Streeter, 2006;& Lauchlan, 2003). Romero (2008) Uche & Maliki (2013) stressed that absenteeism and dropout can be caused by difficult terrain and long distances from school which tempt or force children to withdraw prematurely from school.…”
Section: Introductionmentioning
confidence: 99%
“…School absenteeism is defined as excused or unexcused absences from school by a child (Reid, 2005). Kearny (2008) puts it to be the persistent, habitual, unexpected and unexplained absences from school of a child of compulsory school age. It then implies that absenteeism occurs when a child absents himself from school for whatever reason or when constant learning is interrupted.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Por otro lado, el término de absentismo escolar es un concepto también referente a la inasistencia a la escuela. No obstante, difiere en su carácter reiterado de ausencias injustificadas, no basadas en la ansiedad y llevadas a cabo sin el consentimiento paterno (Kearney, 2008;Kearney y Bensaheb, 2006).…”
Section: Marco Teóricounclassified
“…A sharp distinction is constructed between, on the one hand, active human agents who are regarded as using the software as a pedagogical instrument to improve educational practice, and on the other hand, the passive computer software that is being used. This human-centered and individualistic notion of school absence is evident in much of the literature on truancy and school absence (Huck 2011;Kearney and Bensaheb 2006;Reid 2006;Sommer 1985;Veenstra et al 2010). Contrary to this notion, other researchers have shown that school absence is a multifactored problem, emerging in relations between students, families, the culture of the school and the school environment (Claes et al 2009;Corville-Smith et al 1998;Southwell 2006).…”
mentioning
confidence: 99%